Karakterisasi Sifat Absorbansi Material Menggunakan Metode Spektrofotometri Sinar Ultra Violet dan Visible (UV-Vis) Pada Material Organik: Review Singkat - Salamah, Alifah Balqis; Maharani, Yuliana Juice; Intifadhah, Sahara Hamas (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2025)
In general, organic materials have been studied to have many benefits. One of the benefits of organic materials is that they can be used as the main ingredient for making sunscreen or sun protection, active ingredients in semiconductors, bioreductors, natural coloring materials and others. The Ultra Violet and Visible Light Spectrophotometry (UV-Vis) technique is a technique that has been widely used in research, especially in knowing the potential utilization of organic materials. The purpose of this research is to review various studies that discuss the characterization of organic materials using the Ultra Violet and Visible Light Spectrophotometry (UV-Vis) method to determine the benefits of organic materials by analyzing absorbance values and wavelengths. The method used was a literature study from October 30, 2024 to December 4, 2024. The variables studied in this research are absorbance properties, wavelength and the benefits of organic materials. The results showed that organic materials such as kalakai sprouts and roots have potential as sunscreen, coffee beans have the highest caffeine content, and breadfruit leaves and moringa leaves function as semiconductor active ingredients. Avocado peels produce high flavonoid levels, and coconut shells are effective as a base material for water filters. Water hyacinth and binahong leaves were used in bioreductors and optical property studies of C-dots, while turmeric, moss, pineapple shells and red cabbage were effective as natural colorants. Chili peppers, cacao pods, kalamansi citrus leaves, and soursop leaves were extracted to determine the levels of active compounds